The Influence of Catching Ball Reaction Speed Training on the Reaction Speed of the Goal Keepers - Wildan, Achmad; Supriatna, Supriatna; Widiawati, Prisca (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
This study aims to determine the effect of ball catching reaction speed training on goalkeepers at MI Attaraqqie Malang City students. In this study, 16 meetings were carried out for 6 weeks, and 2 meetings were made forpretest and posttest. The method used in this study is an experimental method that uses a normality test and a T test. The research was carried out at the MI Attaraqqie school and forpretest andposttest conducted on the campus of State University of Malang. The number of samples that took part in the exercise was 5 students at MI Attaraqqie Malang City by using the total population. The instrument used is by using tools whole body reaction. For analysis using the normality test and T test. The results of data analysis were obtained with a value of 0.012> 0.05, , which means that the value is significant. Based on the results of the data analysis conducted, it was stated that there was a significant increase in the ball catching reaction speed exercise on the reaction speed of the goalkeeper at MI Attaraqqie Malang City students.